Experiences, challenges and lessons learnt in medical staff redeployment during response to COVID-19. Issue 2 (8th January 2021) - Sykes, Anny; Pandit, Meghana
Abstract : Background: The response to the COVID-19 pandemic required redeployment of large numbers of staff to avoid acute services being overwhelmed. This unprecedented, previously unplanned redeployment occurred in a rapidly changing environment. This paper describes the process of redeployment at a teaching hospital and assessment of this by the redeployed doctors and redeployment team. Objective: Identify key lessons from the redeployment process to inform resilience and future planning for further COVID-19 peaks. Methods: Redeployment team experiences and challenges were documented in real time and formal structured feedback obtained. All redeployed doctors were asked for quantitative and qualitative feedback regarding their experiences in two distinct acute areas with different approaches to staffing. Results: 63 redeployed staff and five members of the redeployment team completed feedback questionnaires. Most redeployed doctors (76%) were satisfied and had adequate support and training. Redeployment was associated with self-reported stress and anxiety in 95% with 59% describing this as moderate or greater. This was reduced by adequate communication, supervision and a sense of belonging to a firm with access to simple information making a significant difference. Awareness of and satisfaction with well-being support services was also high (71%). The redeployment team identified having a well-mixed team who met daily, an online portal and engagement with leads as the key factors for being successful. Conclusion: Redeployment in response to COVID-19 was associated with reported stress and anxiety in most redeployed doctors. Communication, local induction and feeling valued and being part of a team helped reduce this.